An Evaluation of a Train-the-Trainer Workshop for Social Service Workers to Develop Community-Based Family Interventions - Lai, Agnes Y.; Stewart, Sunita M.; Mui, Moses W.; Wan, Alice; Yew, Carol; Lam, Tai Hing; Chan, Sophia S. (Frontiers in Public Health, 2017)
Introduction: Evaluation studies on train-the-trainer workshops (TTTs) to develop family well-being interventions are limited in the literature. The Logic Model offers a framework to place some important concepts and tools of intervention science in the hands of frontline service providers. This paper reports on the evaluation of the TTT for a large community-based program to enhance family well-being in Hong Kong. Methods: The two-day TTT introduced positive psychology themes (relevant to the programs that the trainees would deliver) and the Logic Model (which provides a framework to guide intervention development and evaluation) to social service workers to guide their community-based family interventions. The effectiveness of the TTT was examined by self-administered questionnaires which assessed trainees’ changes in learning (perceived knowledge, self-efficacy, attitude and intention), trainees’ reactions to training content, knowledge sharing and benefits to their service organizations before and after the training, and then six months and one year later. Missing data were replaced by baseline values in an intention-to-treat analysis. Focus group interviews were conducted approximately six months after training. Results: Fifty-six trainees (79% women) joined the TTT. Forty-four and 31 trainees completed the six-month and one-year questionnaires, respectively. The trainees indicated that the workshop was informative and well-organized. The TTT enhanced trainees’ perceived knowledge, self-efficacy and attitudes towards the application of the Logic Model and positive psychology constructs in program design. These changes were present with small to large effect sizes which persisted to the one year follow-up. The skills learned were used to develop 31 family interventions that were delivered to about 1000 families. Qualitative feedback supported the quantitative results. Conclusion: This TTT offers a practical example of academic-community partnerships that promoted capacity among community social service workers. Goals included sharing basic tools of intervention development and evaluation, and offered therefore the potential of learning skills that extended beyond the lifetime of a single program.